Effect of Ru addition on γ/γ′ microstructural stability in a low-density CoNi based superalloy. (1st February 2022) - Pandey, Prafull; Sawant, Amit; Baler, Nithin; Makineni, Surendra K.; Chattopadhyay, Kamanio
Abstract: The present work explores the effect of ruthenium (Ru) addition to the γ/γ′ strengthened Co-30Ni-10Al-5Mo-2Nb superalloy. A 2 at.% Ru increases the γ/γ′ microstructural stability at 900°C. XRD and APT revealed a reduction of γ/γ′ lattice misfit by ∼ 26% and segregation of Ru at γ/γ′ interface, respectively that contribute to the decrease of γ/γ′ interfacial energy. The temporal evolution of γ′ precipitates at 900°C shows the classical matrix diffusion controlled LSW mechanism with a coarsening rate constant ( K r ) ∼ 6.03 nm 3 /s similar to the values for Co-Al-W based superalloys. Furthermore, Ru addition increases the degree of anomalous strengthening with a peak 0.2% proof stress (PS) value of ∼ 630 MPa at 770°C. The results show Ru as a promising alloying addition to increase the γ/γ′ microstructural stability at high temperatures for the low-density class of CoNi-based superalloys. Graphical abstract: Image, graphical abstract